Effects of Using Pozzolan and Portland Cement in the Treatment of Dispersive Clay - Vakili, A. H.; Selamat, M. R.; Moayedi, H. (Hindawi Publishing Corporation, 2013)
Use of dispersive clay as constructionmaterial requires treatment such as by chemical addition. Treatments to dispersive clay using pozzolan and Portland cement, singly and simultaneously, were carried out in this study.When used alone, the optimum amount of pozzolan required to treat a fully dispersive clay sample was 5%, but the curing time to reduce dispersion potential, from100% to 30% or less, was 3 month long. On the other hand, also when used alone, a 3% cement content was capable of reducing dispersion potential to almost zero percent in only 7 days; and a 2% cement content was capable of achieving similar result in 14 days.However, treatment by cement alone is costly and could jeopardize the long term performance. Thus, a combined 5% pozzolan and 1.5% cement content was found capable of reducing dispersion potential from 100% to zero percent in 14 days. The results indicate that although simultaneous treatment with pozzolan and cement would extend the required curing time in comparison to treatment by cement alone of a higher content, the task could still be carried out in a reasonable period of curing time while avoiding the drawbacks of using either pozzolan or cement alone.